2015
DOI: 10.4236/health.2015.712182
|View full text |Cite
|
Sign up to set email alerts
|

Empathy Levels of Dental Students of Central America and the Caribbean

Abstract: Objective: The aim of this study is to check whether there are differences in the distribution of empathy levels in dental students from nine faculties of dentistry Colombia, Panama, Costa Rica and Dominican Republic. Methods: The levels of empathy and matrices of empathy construct matrices are estimated dental students by using the Jefferson Scale of Physician Empathy, the Spanish version for students (S version) culturally validated in Colombia, Panama, Costa Rica and Dominican Republic measured by arbitrato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 16 publications
5
14
0
5
Order By: Relevance
“…The variability of the empathic response has also been previously observed, by other authors, in the gender variable in students of Dentistry [19][20][21][22] and Medicine. 23 The results observed in this study are consistent with those obtained by the authors mentioned above in terms of the existence of variability of empathic response that seems to be a rule rather than an exception [22][23][24][25][26][27][28] and shows the existence of different models for presentation of the means of empathy within the course estimated in consecutive academic years.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…The variability of the empathic response has also been previously observed, by other authors, in the gender variable in students of Dentistry [19][20][21][22] and Medicine. 23 The results observed in this study are consistent with those obtained by the authors mentioned above in terms of the existence of variability of empathic response that seems to be a rule rather than an exception [22][23][24][25][26][27][28] and shows the existence of different models for presentation of the means of empathy within the course estimated in consecutive academic years.…”
Section: Discussionsupporting
confidence: 51%
“…[19][20][21] In Table 1 the results of the application of regression to the mean values of empathy within the course of the five academic years studied in each of the universities examined are shown. It was found that most of means of the courses at the universities respond to a single type which was cubical, and only one university, a quadratic type (University of San Marcos, Peru).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations